Evaluasi Pendidikan dalam Perspektif Hadits Rasulullah SAW (Afektif dan Psikomotorik) - Khairiah Khairiah (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2021)
Education is a social engineering designed as a conscious and responsible effort to maintain, guide and direct the growth and development of students' lives so that they have true meaning and purpose in life. The educational process is designed with a specific purpose to achieve the desired changes in each student. Islamic education can be understood as education based on the values of Islamic teachings as stated in the Qur'an and al-Hadith as well as in the thoughts of the scholars and in the historical practice of Muslims. In this paper, the author will present matters relating to the evaluation of Islamic education, from the meaning, objectives and functions, principles, goals, and types.